Speechless Cities: Silence and Destruction in German Postwar - Guzmán Rubio, Federico (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2018)
Germany had never experienced such devastation as the one that the air raids left in its cities at the end of Second World War. Despite its magnitude, there are almost no documentary sources that deal with this disaster, and its absence in German historic memory is disturbing. Thinkers such as Enzensberger (2013) and Sebald (2003) have built theories that analyze this phenomenon. From their reflections, the current paper pretends to read two testimonies of this period, I Had Nowhere to Go, by the Lithuanian artist Jonas Mekas, and The Hidden Damage, by Irish writer James Stern, with the purpose of understanding this silence, with the hypothesis that as both authors looked the destruction, they also witnessed the conformation of an intentional oblivion.
Keywords: German postwar; Jonas Mekas; James Stern; historic memory.